Pengaruh Mendengarkan Musik Ambient Terhadap Kecemasan Pasien Ekstraksi Gigi - Elaine S. A. Wanok; Vonny N. S. Wowor; Crista G. Sekeon (e-GiGi, 2026)
Abstract: Tooth extraction is one of the dental procedures which can cause dental anxiety. Dental anxiety can be managed with non-pharmacological interventions such as ambient music. This study aimed to determine the effect of listening to ambient music on patients' anxiety during tooth extraction procedures. This was a true experimental study. Respondents were 30 patients at Tuminting Health Center in Manado, aged 18–59 years, consisting of nine patients who had never undergone tooth extraction and 21 patients who had previously undergone tooth extraction, selected using purposive sampling according to inclusion criteria. Among respondents who had never undergone tooth extraction, the first measurement showed that 44.44% were in low anxiety category, 55.55% in the second measurement, and 66.67% in the third measurement. For moderate anxiety category, the first measurement showed 55.55%, the second measurement 44.44%, and the third measurement 33.33%. Among respondents who had undergone tooth extraction, the first measurement showed low anxiety category was 28.57%, the second measurement was 42.86%, and the third measurement was 28.57%. The moderate anxiety category was 57.14% in the first measurement, 42.86% in the second measurement, and 71.43% in the third measurement. For the high anxiety category, the first and second measurements were 14.28%, and the third measurement was 0%. The Friedman test results showed significant differences in anxiety levels before, during, and after the intervention of ambient music, with an Asymp. Sig. value of 0.001 (<0.05). In conclusion, listening to ambient music effectively reduces anxiety in patients undergoing tooth extraction. Keywords: dental extraction; dental anxiety; ambient music    Abstrak: Ekstraksi gigi merupakan salah satu perawatan yang dapat menyebabkan kecemasan dental. Kecemasan dental dapat ditangani dengan intervensi nonfarmakologis seperti menggunakan musik ambient. Penelitian ini bertujuan untuk mengetahui pengaruh mendengarkan musik ambient terhadap kecemasan pasien saat tindakan ekstraksi gigi. Jenis penelitian ini true experimental. Sampel penelitian berusia 18–59 tahun berjumlah 30 orang pasien di Puskesmas Tuminting Kota Manado, terdiri atas sembilan pasien yang belum pernah menjalani tindakan ekstraksi gigi dan 21 pasien yang sudah pernah menjalani tindakan ekstraksi gigi, diambil dengan purposive sampling sesuai kriteria inklusi. Pada responden yang belum pernah ekstraksi gigi, hasil pengukuran pertama mendapatkan kategori cemas rendah sebesar 44,44%, pengukuran kedua 55,55%, dan pengukuran ketiga 66,67%. Untuk kategori cemas sedang pada pengukuran pertama 55,55%, pengukuran kedua 44,44%, dan pengukuran ketiga 33,33%. Pada responden yang sudah pernah ekstraksi gigi, hasil pengukuran pertama mendapatkan kategori cemas rendah sebesar 28,57%, pengukuran kedua 42,86%, dan pengukuran ketiga  28,57%. Untuk kategori cemas sedang, pengukuran pertama 57,14%, pengukuran kedua 42,86%, pengukuran ketiga 71,43%, sedangkan untuk kategori cemas tinggi, pengukuran pertama dan kedua 14,28% dan pengukuran ketiga 0%. Hasil uji Friedman menunjukkan perbedaan hasil sebelum, saat, dan setelah intervensi menggunakan musik ambient dengan nilai Asymp. Sig. 0,001 (<0,05). Simpulan penelitian ini ialah mendengarkan musik ambient berpengaruh menurunkan kecemasan pasien ekstraksi gigi. Kata kunci: ekstraksi gigi; kecemasan dental; musik ambient